Higher Gas Fuel Utilization Efficiency in Boilers Due to Application of Contact Economizers - G. I. Zhikhar; V. A. Zakrevskiy (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents results of the investigations pertaining to operation of a GM-50-14/250 boiler with a contact economizer. It is shown how a contact economizer influences on fuel saving and reduction of nitrogen oxide effluents.